(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Variations among 45 wheat genotypes were studied on multivariate scale through Mahalanobis D2 statistics at saline and non-saline environments. In the both environment, the genotypes were grouped themselves into five different clusters. Number of genotypes in each cluster varied with the environments. In non-saline environment, cluster II was the largest having 13 genotypes. While, under saline condition, the cluster II also had the highest number of genotypes (16). The distance within cluster were always less than the distances between clusters. The cluster III and IV, I and V and II and V exhibited wide distance between them in non saline, Again cluster III and IV, I and V, I and II and IV and V were distinctly different from others. Cluster mean for yield and its components indicated that twelve genotypes in the cluster V had good performance under non-saline and five genotypes under saline in the cluster IV had good performance. Number of spikes per plant and days to maturity in non-saline environment and number of grains per spike and days to heading in saline environment contributed maximum towards divergence among 45 genotypes. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22216 J. Environ. Sci. & Natural Resources, 7(2): 99-103 2014